2016
DOI: 10.14701/ahbps.2016.20.4.201
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma in choledochal cyst after cystoenterostomy: how a mistreated choledochal cyst can progress to malignancy

Abstract: This case report presents an unusual case of cholangiocarcinoma arising nearly 35 years after cystoduodenostomy for choledochal cyst. The patient visited our hospital with dyspepsia and studies revealed bezoar within the choledochal cyst caused by bile and food reflux. The patient underwent pancreaticoduodenectomy and a biopsy revealed adenocarcinoma, stage IIB. After 19 months, the patient has no recurrence to date and has recovered well. This case shows that proper surgical management and meticulous, long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Cystoenterostomy has been abandoned due to reports of a higher malignant potential compared with complete cyst resection. [44][45][46] In 1980, Yamaguchi recommended the total excision for the prevention of ascending cholangitis, cystolithiasis, and malignant transformation following an analysis of 1.433 patients from the Japanese literature, and Lilly reported on the superiority of total cyst excision due to simultaneous treatment of coexisting biliary malformations. 47,48 Additionally, according to Filler and Stringel, total excision should be preferred for the elimination of bile stasis, prevention of chronic pancreatic reflux into the cyst, and the prevention of cancer.…”
Section: Operation Methodsmentioning
confidence: 99%
“…Cystoenterostomy has been abandoned due to reports of a higher malignant potential compared with complete cyst resection. [44][45][46] In 1980, Yamaguchi recommended the total excision for the prevention of ascending cholangitis, cystolithiasis, and malignant transformation following an analysis of 1.433 patients from the Japanese literature, and Lilly reported on the superiority of total cyst excision due to simultaneous treatment of coexisting biliary malformations. 47,48 Additionally, according to Filler and Stringel, total excision should be preferred for the elimination of bile stasis, prevention of chronic pancreatic reflux into the cyst, and the prevention of cancer.…”
Section: Operation Methodsmentioning
confidence: 99%
“…The earlier drainage procedures have been long abandoned due to the high rate of malignancies that ensue, especially when internal drainage operations are used. It has been reported that patients who have had previous internal drainage operations developed malignancies at relatively young ages (32,33), a circumstance in which enterokinase was implicated. It has been postulated that the enterokinase enhances the activation of refluxed pancreatic enzymes, consequently accelerating the destruction of biliary epithelium (34).…”
Section: Discussionmentioning
confidence: 99%
“…Namun, risiko terjadinya karsinoma saluran bilier setelah pasien CC menjalani reseksi berkisar antara 0.7-6%. [7,8] Pasien CC yang ditangani sampai usia 10 tahunmemiliki risiko terjadi karsinoma saluran bilier sebesar 0,7%, antara usia 10-20 tahun sebesar 6,8% dan usia lebih 20 tahun sebesar 14,3%. Patogenesis terjadinya keganasan saluran bilier diperkirakan karena refluks cairan pankreas ke saluran bilier sehingga epitel saluran bilier mengalami inflamasi kronis dan perubahan ke arah keganasan.…”
Section: Pendahuluanunclassified